2021
DOI: 10.1523/jneurosci.2744-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Cue and Reward Evoked Dopamine Activity Is Necessary for Maintaining Learned Pavlovian Associations

Abstract: Associating natural rewards with predictive environmental cues is crucial for survival. Dopamine (DA) neurons of the ventral tegmental area (VTA) are thought to play a crucial role in this process by encoding reward prediction errors (RPEs) that have been hypothesized to play a role in associative learning. However, it is unclear whether this signal is still necessary after animals have acquired a cue-reward association. In order to investigate this, we trained mice to learn a Pavlovian cue-reward association.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Adolescent VTA and SN neurons are engaged differently to reach the same behavioral endpoints as adults Dopamine neurons in the VTA and SN have been implicated in operant and Pavlovian conditioning (Schultz, 1998;Dalley et al, 2002;Parkinson et al, 2002;Haruno and Kawato, 2006;Lex and Hauber, 2010;Coddington and Dudman, 2018;Keiflin et al, 2019;van Zessen et al, 2021). While much of the learning literature has focused on dopamine neurons in the VTA, multiple studies indicated that SN neurons also generate reward-related signals (Coddington and Dudman, 2018;Saunders et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescent VTA and SN neurons are engaged differently to reach the same behavioral endpoints as adults Dopamine neurons in the VTA and SN have been implicated in operant and Pavlovian conditioning (Schultz, 1998;Dalley et al, 2002;Parkinson et al, 2002;Haruno and Kawato, 2006;Lex and Hauber, 2010;Coddington and Dudman, 2018;Keiflin et al, 2019;van Zessen et al, 2021). While much of the learning literature has focused on dopamine neurons in the VTA, multiple studies indicated that SN neurons also generate reward-related signals (Coddington and Dudman, 2018;Saunders et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the adult brain, dopamine neurons in the VTA, which project primarily to ventral (limbic) striatal regions and represent state and action values as well as reward prediction errors, are important for reward signaling during both types of conditioning (Schultz, 1998;Pessiglione et al, 2006;Keiflin et al, 2019). Emerging data suggest that adult dopamine neurons in another midbrain region, the substantia nigra (SN), are also involved in processing reward-related learning (Coddington and Dudman, 2018;Keiflin et al, 2019;van Zessen et al, 2021). Dopamine neurons in SN primarily project to the dorsal striatum (DS).…”
Section: Introductionmentioning
confidence: 99%
“…3 show that cholinergic input facilitates glutamatergic inputs induced resonator BS, indicating that glutamatergic (cholinergic) inputs can regulate the scale of glutamatergic-(cholinergic-) induced resonator BS originating from other brain regions and cholinergic inputs can regulate the scale of glutamatergic-induced resonator BS, thereby producing different amplitude of phasic DA release. In experiments, it is observed that the amplitude of DA release varies due to different reward stimuli [61] [62]. The other speculation is that, BA state would induce DA ramping signals.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, several causal manipulations also highlight the direct involvement of DA system in reward learning and motivational processes. For example optogenetics activation or inhibition of DA midbrain neurons during a task where subjects need to learn the value of different stimuli will, respectively increase or decrease the value of the stimuli and ultimately modulate the subjects' motivation to acquire these stimuli and their associated reward (Stauffer et al, 2016;Van Zessen et al, 2021). Finally, the opposite neuro-behavioral mechanism can be observed during the presentation of a conditioned stimulus predicting an aversive event.…”
Section: Promoting Appetitive Reward Seeking and Aversive Event Avoid...mentioning
confidence: 99%